Assessment and Evaluation for Learners in Multilingual Societies at Technical Civil Engineering Ekasakti University - Marmai, Ungsi A.O.; Suri, Elda Martha (J-SHMIC : Journal of English for Academic, 2016)
This analysis examines some of the problems that are faced by teachers and students in the teaching and learning of English for special purposes (ESP) in multilingual nations. A survey recently found that although 98 percent knew that English was the sole language of instruction at the institution, only 49 percent expected to study English as a subject in any form as part of their curriculum. Many students looked upon English as a subject of study necessary only to gain entrance into the university, and had little motivation to study it past the secondary level. Other problems faced by teachers and students include the multilingual background of the learners, lack of cooperation from teachers of other subjects, the need to import language materials, poor levels of language teacher training, and large class sizes. An alternative approach to ESP is suggested, one in which the learner's native language and other languages in the learner's environment play a major role in tertiary education. The importation of culturally and educationally irrelevant materials is noted along with the urgent need for teacher training reform.